Додержання права осіб, що страждають психічними розладами, на справедливий суд - Тельнова, Аліна Анатоліївна (Гуманітарні аспекти цифрового суспільства : тези доп. учасників міжн. наук.-практ. конф. (Харків, 8 груд. 2022 р.), 2022)
This article is devoted to the evaluation of the effectiveness of the judicial system of Ukraine in relation to persons suffering from mental disorders. The basic laws that guide the choice of punishment, as well as conflicts in them, are considered.